Theory of everything the origin and fate of the universe - Hawking Stephen W (Mumbai Jaico, 2006)
In this book Hawking presents a series of seven lectures in which he lays out, perhaps more clearly and concisely than ever, the history of the universe as we know it. He offers, for all who would take it, a voyage of discovery about the cosmos and our p
Special anniversary edition
Keywords: Cosmology; Science-philosophy